Climate change and the extractives sector - Tony Addison (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The extractives industries must adjust their operations to shifting patterns of demand for oil, natural gas, and coal together with metals and minerals - as policies and new technologies encourage progress along low-carbon pathways in energy, transportation and construction to combat climate change. Adoption of renewable energy is accelerating across the world, but fossil fuels will be in use for many years (with natural gas replacing coal in electricity generation, especially in Asia). Large amounts of fossil-fuels will eventually be unusable ("stranded") if international goals to contain greenhouse gas emissions are to be met. Low-carbon technologies and pathways are likely to be more intensive in metals and materials than existing fossil-fuel technologies. This offers great opportunities for countries with mining sectors, but there are major concerns over the distribution of the economic benefits, and mining itself must reduce its environmental footprint together with its own greenhouse gas emissions.
Keywords: 330; extractives; oil; natural gas; coal; metals; energy; climate change